The Templeton twins make a scene - Weiner, Ellis (Weiner, Ellis. Templeton twins, 2013)
Professor Templeton has been hired by the Thespian Academy of the Performing Arts and Sciences to invent something, anything, important (and profitable) but the thirteen-year-old twins, Abigail and John, are suspicious and determined to investigate.